2014
DOI: 10.1002/2014jd021797
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in physical processes controlling evaporation over inland water

Abstract: While previous studies have shown the distinct characteristics of water surface energy fluxes in different seasons, much less analysis is conducted about how seasonal changes in physical processes and environmental variables in the atmospheric surface layer (ASL) cause variations in flux exchange.Here we analyzed and compared eddy covariance fluxes of sensible heat (H) and latent heat (LE) and other microclimate variables that were measured over a large inland water surface in the winter season (January, Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
(100 reference statements)
5
25
0
Order By: Relevance
“…The post-field data processing procedures are documented elsewhere (Zhang et al 2010, Zhang and Liu 2014, Gao et al 2016. Briefly, these procedures include: 1) removing physically impossible values and spikes from the time series; 2) double rotation for the sonic anemometer measured w (Kaimal and Finnigan 1994); 3) calculation of averages, variances and covariances using a 30 min block average; 4) sonic temperature correction (Schotanus et al 1983, Liu et al 2001, oxygen cross sensitivity correction for KH20 (Tanner et al 1993), density correction applied to LE (Webb et al 1980), and correction for flux attenuation due to spatial separation of CSAT3 and KH20 ; and 5) quality check for stationary and developed turbulent conditions (Foken et al 2004).…”
Section: Post-field Data Processingmentioning
confidence: 99%
“…The post-field data processing procedures are documented elsewhere (Zhang et al 2010, Zhang and Liu 2014, Gao et al 2016. Briefly, these procedures include: 1) removing physically impossible values and spikes from the time series; 2) double rotation for the sonic anemometer measured w (Kaimal and Finnigan 1994); 3) calculation of averages, variances and covariances using a 30 min block average; 4) sonic temperature correction (Schotanus et al 1983, Liu et al 2001, oxygen cross sensitivity correction for KH20 (Tanner et al 1993), density correction applied to LE (Webb et al 1980), and correction for flux attenuation due to spatial separation of CSAT3 and KH20 ; and 5) quality check for stationary and developed turbulent conditions (Foken et al 2004).…”
Section: Post-field Data Processingmentioning
confidence: 99%
“…As is well understood, latent heat fluxes ( LE ; with E as evaporation, in other words) and sensible heat fluxes ( H ) from lakes are primarily controlled by water vapor and temperature gradients, together with turbulent mixing intensity, which is influenced by surface roughness length, wind speed, and atmospheric stability [ Assouline et al ., ; Blanken et al ., ; Blanken et al ., ; Granger and Hedstrom , ; Heikinheimo et al ., ; Liu et al ., ; Rouse et al ., ; Wang et al ., ; Zhang and Liu , ]. The question of what factors drive turbulent flux exchange between lakes and the atmosphere remains highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the widely observed positive correlations between temperature and water vapor gradients on the one hand and sensible and latent heat fluxes on the other [ Blanken et al ., ; Blanken et al ., ; Liu et al ., ; Liu et al ., ; Liu et al ., ; Zhang and Liu , ], net radiation is an important parameter for estimating evaporation over longer periods, such as 1 day, 10 days, or 1 month [ Rosenberry et al ., ; Yao , ]. However, no clear positive correlations have been observed between net radiation and turbulent heat flux in deep or large lakes [ Blanken et al ., ; Blanken et al ., ; Liu et al ., ; Zhang and Liu , ]. This result contrasts with the positive correlations from shallow lakes over periods longer than a week [ Granger and Hedstrom , ; Nordbo et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed that the diurnal LE and H variations in lakes are out of phase with net radiation ( R n ) and are primarily governed by the wind speed, temperature, and humidity gradient of the atmospheric surface layer (Assouline et al, ; Granger & Hedstrom, ; Lenters et al, ; Nordbo et al, ; Q. Zhang & Liu, ). The relationships can be described using the bulk aerodynamic methods (Garratt, ; Stull, ).…”
Section: Introductionmentioning
confidence: 99%